2022
DOI: 10.2355/isijinternational.isijint-2021-393
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Measurement for the Inclusion Analysis of Steel Materials in Emission Spectrometry

Abstract: This paper reviews three emission spectrometric methods that can be applicable to the inclusion analysis in steel materials, which provides information on the number, the size and distribution, as well as the chemical composition of inclusion particles. Cathodoluminescence (CL), X-ray-excited optical luminescence (XEOL), and beam-scanning laser-induced breakdown spectrometry (LIBS) are employed for the imaging measurement of the inclusions. As a typical specimen, alumina inclusions are evaluated to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The model sample was prepared by melting metal powders consisting of stainless-steel (Fe, Cr, Ni, and Mn) and a metal deoxidizer (Al) under inert gas atmosphere. [21,24,25,36] Half of a mixture of 68 mass pct electrolytic Fe powder (purity: 95 pct, Wako Pure Chemical Industries, Ltd., Osaka, Japan), 20 mass pct Cr powder (purity: 99.9 pct, Kojundo Chemical Laboratory Co., Ltd., Saitama, Japan), 10 mass pct Ni powder (purity: 99 pct, Wako Pure Chemical Industries, Ltd., Osaka, Japan), 1 mass pct Mn powder (purity: 99.9 pct, Kojundo Chemical Laboratory Co., Ltd., Saitama, Japan) were first placed in a MgO crucible, and 1 mass pct Al powder (purity: 99.9 pct, Kojundo Chemical Laboratory Co., Ltd., Saitama, Japan) was placed on the mixture. Next, the remaining half of the mixture was placed on the Al powder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model sample was prepared by melting metal powders consisting of stainless-steel (Fe, Cr, Ni, and Mn) and a metal deoxidizer (Al) under inert gas atmosphere. [21,24,25,36] Half of a mixture of 68 mass pct electrolytic Fe powder (purity: 95 pct, Wako Pure Chemical Industries, Ltd., Osaka, Japan), 20 mass pct Cr powder (purity: 99.9 pct, Kojundo Chemical Laboratory Co., Ltd., Saitama, Japan), 10 mass pct Ni powder (purity: 99 pct, Wako Pure Chemical Industries, Ltd., Osaka, Japan), 1 mass pct Mn powder (purity: 99.9 pct, Kojundo Chemical Laboratory Co., Ltd., Saitama, Japan) were first placed in a MgO crucible, and 1 mass pct Al powder (purity: 99.9 pct, Kojundo Chemical Laboratory Co., Ltd., Saitama, Japan) was placed on the mixture. Next, the remaining half of the mixture was placed on the Al powder.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have been reported on IL three-dimensional imaging; for example, a study was conducted for the acquisition of surface structural information of luminescent samples (e.g., lapis lazuli) using IL. [20] The author previously demonstrated that cathodoluminescence (CL) imaging, which uses the same mechanism as IL but with electron bombardment instead of ion bombardment, can provide two-dimensional images of non-metallic inclusions in steels, such as MgOAEAl 2 O 3 spinel, [21][22][23][24] Al 2 O 3 , [21][22][23][24] calcium aluminates, [25] rare-earth oxides (La 2 O 3 , CeO 2 , and Nd 2 O 3 ), [26] CaS, [25] BN, [27] and AlN [27] inclusions. This indicates that the IL images of these non-metallic inclusions could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…A paper by Imashuku and Wagatsuma reviewed (with 66 refs) three emission spectrometric techniques, namely cathodoluminescence, X-ray excited optical luminescence (XEOL) and LIBS that have been used for such an analysis. 26 The review provides a convenient table summarising the abilities of each of the techniques along with their attributes and drawbacks and then gives individual sections on each technique. It was concluded that LIBS offers the best opportunity for on-line analysis because it does not require a vacuum or any sample pretreatment.…”
Section: Ferrous Metalsmentioning
confidence: 99%
“…Laser ablation absorption or fluorescence spectroscopies are powerful tools for the direct analysis of solid samples. [11][12][13][14] However, upon irradiation of the surface with an intense laser beam, the translational temperatures of the atoms ejected into the plasma plume reach 5 000 − 10 000 K, and at this temperature, the isotopic shift of 88 Sr-90 Sr (206.2 MHz) cannot be resolved due to broadening of the spectral peaks. This study's authors recently developed a novel analytical instrument that combines diode laser absorption spectroscopy with a supersonic plasma jet.…”
Section: Introductionmentioning
confidence: 99%